Competitor Intelligence Profiling Framework for Shipping Industry - Kanellopoulos, Anastasios Nikolaos (HAPSc Policy Briefs Series, 2025)
This study introduces a conceptual Competitor Intelligence profiling framework aimed at enhancing strategic decision-making for Shipping companies operating in a dynamic and highly competitive global market. With the Shipping industry increasingly influenced by globalization, technological advancements, and fluctuating economic conditions, companies must adopt a proactive approach to gain insights into competitors' strategies, capabilities, and market positioning. The proposed framework guides companies through four key steps: identifying competitors’ current strategies and capabilities, analyzing micro and macro environmental factors, forecasting future trends, and benchmarking against technological innovators. By applying this framework, Shipping companies can improve their ability to anticipate market shifts, identify potential growth opportunities, and make informed strategic decisions that foster long-term competitiveness. This approach provides a structured and comprehensive methodology for competitor analysis in the Shipping industry, helping companies navigate the complexities of a fast-evolving business landscape. The study emphasizes the critical role of competitive intelligence in sustaining a competitive edge in the sector.